Competitiveness Evaluation Method of Supersonic Civil Aircraft Based on Analytic Hierarchy Process - Jiazheng He; Rui Pan; Wenyuan Cheng; Chenxin Guo; Zhijun Meng (Aerospace)
As the demand for long-distance flights continues to increase, supersonic transport (SST) has once again become a hot research topic. However, in the conventional research on competitiveness of civil aircraft, because the flight speeds of various subsonic aircraft are relatively close, the influence of flight time on comfort is less considered. Therefore, there is a lack of evaluation methods considering time comfort to comprehensively evaluate supersonic and subsonic civil aircraft. This paper proposed an evaluation method for the competitiveness of supersonic civil aircraft based on the Analytic Hierarchy Process (AHP). Key indicators were selected to form a competitiveness evaluation model from the perspective of four criterion factors of economy, comfort, adaptability, and environment. Based on the key indicators, we have proposed a type of supersonic aircraft. The expected SST might have a much stronger market competitiveness compared to the Concorde, and it could provide a 43.5% improvement in passenger comfort over the Airbus A350 in long-distance flights. And the expected SST could outperform the Gulfstream G650 in economic feasibility. The evaluation method proposed in this paper could reflect the characteristics of supersonic civil aircraft and other subsonic aircraft, and effectively compare their competitiveness. This work can be used to evaluate the social acceptance of supersonic civil aircraft, help to optimize the overall design of supersonic civil aircraft, and provide reliable decision-making support for airline aircraft selection.